The influence of transport infrastructures on land-use conversion decisions within municipal plans - Padeiro, Miguel (Journal of Transport and Land Use, 2014)
Transit-oriented development (TOD) is one of the most popular means of public intervention in the field of spatial planning, which aims at reducing land consumption caused by urban sprawl. In this paper, a logit model is computed to assess whether the Municipal Master Plans approved during the 1990s in the Lisbon region (Portugal), currently in force, contemplated public transit stations as a relevant requirement for the location of the planned urban expansion areas and, more specifically, for the conversion of non-urban areas to artificialized areas. It is shown that TOD was not taken as a preferential approach, suggesting that there may be at the outset an inherent resistance to public injunctions on limiting land-use conversion, regardless of other obstacles frequently mentioned.